2019
DOI: 10.4236/ojepi.2019.92011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus and Associated Risk Factors among Inmates at New Bell Prison, Douala, Cameroon

Abstract: Although a high prevalence of HCV infection in correctional facilities has been well reported in several countries around the world, there has been no such data from Cameroon. The aim of this study was to determine the prevalence and factors associated with viral hepatitis C seropositivity among prisoners incarcerated at the New Bell Central Prison in Douala. From the 2 nd to the 27 th of July 2018, 940 inmates selected using a systematic random sampling method were interviewed to collect data on sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…When paralleled with international studies, the prevalence is higher than studies from India (1.27%) [31], West Africa (0.5%) [32], Turkey (0.5%) [33] and Ethiopia (1.2%) [27]. On the contrary, the prevalence study is lower than studies from Ghana (19.2%) [25], Brazil (13.6%) [34], Pakistan (15.2%) [26], Mexico (4.6%) [35], Cameroun (4.4%) [36] and Spain (22.7%) [37]. The pragmatic differences in this prevalence could be due to the population size tested, the condition of the prison, high-risk behaviours such as injection drug use, homosexuality, and the screening method could also impact the differences [38] [39].…”
Section: Discussionmentioning
confidence: 59%
“…When paralleled with international studies, the prevalence is higher than studies from India (1.27%) [31], West Africa (0.5%) [32], Turkey (0.5%) [33] and Ethiopia (1.2%) [27]. On the contrary, the prevalence study is lower than studies from Ghana (19.2%) [25], Brazil (13.6%) [34], Pakistan (15.2%) [26], Mexico (4.6%) [35], Cameroun (4.4%) [36] and Spain (22.7%) [37]. The pragmatic differences in this prevalence could be due to the population size tested, the condition of the prison, high-risk behaviours such as injection drug use, homosexuality, and the screening method could also impact the differences [38] [39].…”
Section: Discussionmentioning
confidence: 59%
“…This can be supported by the fact that HCV can survive on surfaces such as needles, lancet pens, lancets, and glucometers on average for five to seven days [14]. As such, there is a high possibility of being infected when there is inadequate sterilization of medical equipment and sharp objects such as needles, razor blades, toothbrushes, or other household articles like shaving machines, tattooing, and body piercing [5,17,18], this advocates the significantly high prevalence seen among DM patients sharing sharp objects (9.1%), those with Tattoos (9.4%), scarification (3.6%), participants who have been hospitalized (6.7%) and had a blood transfusion (25.0%) at least once. To further attest to this, our data showed that the higher occurrence of HCV was seen in those with a family history of HCV (19.2%) compared to their counterpart (0.6%), suggesting that there is likely intra-household viral transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The male sex was the most affected by HCV (6.3%), without a significant association being found. Kowo et al [13] also found HCV infection to be more prevalent among men than women. Kowo et al's study of the prison population in which the majority of prisoners are men (86.7%), could explain their results.…”
Section: Prevalence Of Hcv-abmentioning
confidence: 95%
“…In fact, this prevalence was higher in the age group over 50 years with a frequency of 19.8%. Kowo et al [13] reported in 2019 a risk 4 times higher in people over the age of 50. Similar results have been reported by several African literatures, including Baha et al [14] in Morocco, Elzouki et al [15] in Libya and Kandeel et al [16] in Egypt.…”
Section: Prevalence Of Hcv-abmentioning
confidence: 97%
See 1 more Smart Citation